Permainan Kartu Pilah sebagai Media Promosi Kesehatan terhadap Pengetahuan dan Praktik Pemilahan Sampah pada Santri Remaja di Pondok Pesantren Krapyak - Dzakirotillah Dzakirotillah; Bambang Suwerda; Siti Hani Istiqomah (Sanitasi: Jurnal Kesehatan Lingkungan, 2018)
Waste sorting has to be implemented at initial waste generators/producers, including schools, such as islamic boarding school (IBS) or pesantren. Most of students in Krapyak IBS have low knowledge and inappropriate practice of waste sorting. One of the efforts to overcome this problem is by conducting health promotion. This research was aimed to know the effect of sortingcard game as the media of health promotion towards Krapyak IBS students’ knowledge and practice on waste sorting. The study was a quasi-experiment with non-equivalent control groupdesign. The study subjects were 52 students aged 13-18 years old. They were divided into 2 groups, i.e. 26 were assingned into treatment group and the other 26 into the control group. Statistical analysis by using independent t-test and Mann-Whitney at ?=0,05 show that the knowledge and practice scores between pre-test and post-test are statistically significant (the obtained p-values were 0,043 and 0,040, respectively). By using sorting card game, students’ knowledgeincreased 55,14 % and the practice increased 67,23 %.